PR-CAMPAIGN PLANNING ON THE EXAMPLE OF A NON-GOVERNMENTAL ORGANIZATION - Boryshkevych , I. I.; Piatnychuk , I. D. (The actual problems of regional economy development, 2022)
PR is a multifaceted activity to achieve goals, regardless of industry. It is necessary to highlight the value of PR through the prism of public opinion, which is the subject of study and analysis of PR management. It is public opinion that provides an opportunity to move to dialogue in public relations and various economic structures. After all, in a democratic society, no significant changes are possible without studying public opinion and agreeing with civil society. PR also includes image, reputation and brand. The article discusses the theoretical foundations of public relations. The algorithm of planning and implementation of PR-campaign through the RACE formula: research, action, communication and evaluation is given. The stages of PR-campaign planning are covered, which include: setting the problem, goals and objectives of the PR-campaign, defining the target audience, selecting communication channels and testing, forming an action plan and evaluating the effectiveness of the PR-campaign. The PR-campaign was planned on the example of the non-governmental organization “School of Business and Management”. The problem to be solved is defined, the purpose, tasks and target audience are defined. The main channels of communication included: promotion through the official website of the non-governmental organization “School of Business and Management”, dissemination of information on social networks (Facebook and Instagram) and thematic events. Based on the results of the competitiveness benchmarking, a new structure of the official website of the educational public organization was proposed. The peculiarities of SMM promotion, the advantages of using targeted advertising and the use of the Internet in PR are studied. A content plan of publications for the researched non-governmental organization has been developed. It is proposed to hold events for the non-governmental organization “School of Business and Management” in the form of open trainings or webinars. Event management promotes the organization’s services and increases its recognizability.